PERANCANGAN SISTEM APLIKASI PEMBELIAN DI TIKTOK SHOP DENGAN MENGGUNAKAN SOFTWARE “STAR UML”USE CASE DIAGRAM”ACTIVITY DIAGRAM”CLASS DIAGRAN”NORMALISASI FILE”MS.ACCESS - Tomi Saputra; Aditya Dwi Angga. S, Sulthan Muhamad Maulidin, Febrian Alfaridz, M. Rahmat Fadilah (CV. Adiba Aisha Amira, 2024)
TikTok is gradually moving forward to become a more commercialized social media platform. As time progresses, Tiktok is used not only as entertainment but also as a new digital marketing tool. Because it is equipped with the Tiktok Shop feature, Tiktok is quickly noticed by business people. This research discusses the role of using live streaming and TikTok affiliates in the Tiktok application as an eflort to increase followers and sales at Moodels. This research data was taken from internal data resulting from sales and increasing followers by applying several patterns to Moodels over a certain period of time. The results confirm that live streaming and TikTok affiliates can increase followers and sales on Moodels. With live streaming and TikTok affiliates, potential customers have something to consider before buying a product.